INTERCULTURAL SURVIVAL STRATEGIES OF FARMERS AFFECTED BY THE ERUPTION OF MOUNT SINABUNG: A SOCIOECONOMIC ANALYSIS OF DECISIONS TO CHOOSE TEMPORARY - Sinar Indera Kesuma (Journal of Oral Traditions, 2025)
This study explores the survival strategies adopted by farmers affected by the eruption of Mount Sinabung, with a particular focus on their decision-making processes regarding temporary employment during the displacement period. The research was conducted in Karo Regency, North Sumatra, encompassing farmers from the villages of Guru Kinayan, Gamber, Kuta Tonggal, and Beras Tepu. Utilizing a quantitative approach and survey method, 63 displaced farmers were analyzed using Chi-Square tests and Paired Sample T-tests. The results revealed that additional skills, number of dependents, participation in customary activities, and temporary housing status significantly influenced job choice. These findings are crucial for informing refugee empowerment policies that are rooted in local potential and actual needs